2022
DOI: 10.1542/peds.2021-053706
|View full text |Cite
|
Sign up to set email alerts
|

Child Opportunity Index and Changes in Pediatric Acute Care Utilization in the COVID-19 Pandemic

Abstract: BACKGROUND Pediatric acute care utilization decreased dramatically during the COVID-19 pandemic. This study examined the association between the Child Opportunity Index (COI), a multidimensional neighborhood measure of childhood opportunity, and changes in acute care utilization at US pediatric hospitals during the COVID-19 pandemic compared to the prior three years. METHODS This observational study utilized administrative da… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 21 publications
(10 citation statements)
references
References 31 publications
1
9
0
Order By: Relevance
“…Two studies assessing pediatric acute care utilization and elective surgical access during the early stages of the pandemic found that patients from the lowest COI level had the highest reduction in care compared with patients from higher COI levels,. 13,14 In contrast, another study found that families who were of a race other than White, spoke a language other than English, were publicly insured, and were from low COI levels had the highest hesitancy to seek care during COVID-19. 15 Current research depicts COI as an indicator for reduced care, aligning with the findings of this study that highlights COI as a possible predictor for reduced pediatric surgical care access.…”
Section: Discussionmentioning
confidence: 99%
“…Two studies assessing pediatric acute care utilization and elective surgical access during the early stages of the pandemic found that patients from the lowest COI level had the highest reduction in care compared with patients from higher COI levels,. 13,14 In contrast, another study found that families who were of a race other than White, spoke a language other than English, were publicly insured, and were from low COI levels had the highest hesitancy to seek care during COVID-19. 15 Current research depicts COI as an indicator for reduced care, aligning with the findings of this study that highlights COI as a possible predictor for reduced pediatric surgical care access.…”
Section: Discussionmentioning
confidence: 99%
“…Percentage of household poverty was also negatively associated with school age vaccination rates which is consistent with previous work looking at vaccination coverage and healthcare utilization during the pandemic. 8,26…”
Section: Discussionmentioning
confidence: 99%
“…Health-related social factors. Geocoded PEDSnet EHR data were linked to data from two indices measuring neighborhood level socio-economic and environmental resources and exposures, the Area Deprivation Index (ADI) and the Child Opportunity Index (COI) (19,20) , at the Census block group level.…”
Section: Primary Independent Variablesmentioning
confidence: 99%